2015
DOI: 10.1108/ijchm-09-2013-0413
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining perceived usefulness and ease of use in online booking

Abstract: Purpose – This paper aims to report the findings of an empirical research focusing on Hong Kong online users’ intention to book online tourism products with latest figures. Focusing on the technology acceptance model (TAM), this case study extends the recent research with providing insight regarding the online users’ perceptions of TAM dimensions and how these dimensions are perceived among different demographic groups and Internet usage characteristics with latest figures in Hong Kong, a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
3
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 36 publications
9
86
3
13
Order By: Relevance
“…Low levels of ease of use generate errors and such errors increase feelings of distrust and discourage future transactions. In e-commerce, ease of use influences perceived competence and trust (Flavi an et al, 2006;Kucukusta et al, 2015). It is expected that if an OSN website is easy to use and navigate, users will tend generate trust to the website.…”
Section: Perceived Ease Of Use and Belief In Integritymentioning
confidence: 98%
See 1 more Smart Citation
“…Low levels of ease of use generate errors and such errors increase feelings of distrust and discourage future transactions. In e-commerce, ease of use influences perceived competence and trust (Flavi an et al, 2006;Kucukusta et al, 2015). It is expected that if an OSN website is easy to use and navigate, users will tend generate trust to the website.…”
Section: Perceived Ease Of Use and Belief In Integritymentioning
confidence: 98%
“…Ajzen (1974, 1975) suggest that subjective norms exert pressures on an individual to complete a specific behavior. The theory of reasoned action asserts that individuals' behavioral intentions are determined by their attitude toward the behavior and their subjective norm (Kucukusta, Law, Besbes, & Legoh erel, 2015). Ajzen (1991) defines subjective norm as "the perceived social pressure to perform or not to perform the behavior in question" (p. 188).…”
Section: Perceived Ease Of Use and Subjective Normsmentioning
confidence: 99%
“…During the pre-trip stage, tourists consume contents for their travel decision-making [47]. Tourists use STTs for their tourism information search [48], products and service booking [49], and online travel commerce [50]. After their trips, tourists may share their experiences, products, and services by means of photos, comments, and reviews, which can be accessed by others [51].…”
Section: Communication Factors Affecting the Travelers Intention To Umentioning
confidence: 99%
“…Robey (1979) theorized that a system that does not help users perform their jobs is not likely to be received valuably, in spite of careful implementation efforts. Prior research provides the theoretical premises that underlie the relationship between perceived usefulness and user acceptance (e.g., Davis et al, 1989) and substantial empirical evidence was found in support of the significant impact of perceived usefulness on behavioral intentions (e.g., Calisir, Gumussoy, Bayraktaroglu, & Karaali, 2014;Davis, 1989;Davis et al, 1989;Kim & Lee, 2014;Kucukusta, Law, Besbes, & Legohérel, 2015;Rana, Dwivedi, Williams, & Weerakkody, 2015;Venkatesh & Davis, 1996). Similarly, studies (e.g., Joo et al, 2011;Kim & Lee, 2014;Rai, Lang, & Welker, 2002;Seddon, 1997) establishing IS success have theorized the relationship between perceived usefulness and user satisfaction.…”
Section: Hypotheses Developmentmentioning
confidence: 99%